The Urgency the Role of Amicus Curiae in the Eradication of Land Mafia Crimes - Ahmad Hadi Prayitno (Faculty of Law, Universitas Pekalongan, 2023)
Amicus curiae is needed by the development of judicial practice in our country. This is as a result of the crime development which is more completed and massive. The existence of amicus curiae is expected to find the answers in every deadlock situation that occurs in the case examination process. It is including on land mafia. They do it through digital media, carried out by actors who have skills and good knowledge in law , and has carried out by people who have access to land documents. It cannot be considered ordinary and also cannot be enforced with ordinary law enforcement methods. The design of this article was qualitative law research. Based on the research before, It can concluded that the criminal mode of the land mafia is not in general but specific in land documentation. It also uses technological advances to change the administrative data of land registration and the land ownership. They also use specialized knowledge about land, which is not always mastered by criminal law experts. This condition showed that Amicu Curie is needed to solve criminal cases that have a more complicated mode, if compared it to traditional crimes. The existence of amicus curiae in the eradication of land mafia cases has not been yet recognized by legislation, either in the context of Technical Guidelines Number: 01/Juknis/D.VII/2018 on the prevention and eradication of Land Mafia or in the Criminal Procedure Code. Therefore, the term of amicus curiae is not formally found in Indonesian criminal legislation. The judges and prosecutors ignore the role of amicus curie and is different with expert witnesses who are juridically recognized and required to be present by legal mechanisms.